Aníbal Quijano: orígenes de sus luchas contra el poder - Valladares Quijano, Manuel (2019)
This paper presents the life and academic work of a Peruvian (Latin American) thinker and social theorist from San Marcos (UNMSM). It shows significant moments of his life, research work in sociology, and production of theoretical proposals on modernity and coloniality of power. Includes unpublished photos about the social and family life of a thinker whose political experience faced the civilizing Eurocentric cultural model and global neoliberalism.